High-temperature aluminum composite materials with special physical and mechanical properties produced by mechanical alloying - F. G. Lovshenco; I. A. Lozikov; A. I. Khabibulin (Литьë и металлургия)
High-temperature aluminum composite materials with special physical and mechanical properties produced by mechanical alloying. The study is aimed at making high-temperature aluminum composite materials with special physical and mechanical properties. An effective way to solve the problem is to use a technology based on reactive mechanical alloying. The processes of phase composition formation, the structure and properties that occur at all stages of the technology implementation and the effect of alloying components on these processes have been analyzed, and the composition «aluminum (PA4) – surfactant (С17Н35СООН – 0.7 %)» has been found to be the most appropriate. The microcrystalline structure of its base, regardless of the composition of constituent materials, is preserved at subsequent stages of production of materials and determines high values of high-temperature strength, which are significantly higher than those of analogue materials. The microcrystalline structure of the base is characterized by a well-developed surface of grain and subgrain boundaries and is stabilized by nanosized inclusions of aluminum oxides and carbides formed during mechanical alloying. Additional alloying, which provides special properties, does not change the «structural phase» type of the developed materials. They are considered to be dispersion hardened composite microcrystalline materials.